Pravopisno slovaropisje na Inštitutu za slovenski jezik Frana Ramovša ZRC SAZU - Dobrovoljc, Helena; Bizjak Končar, Aleksandra (Slavia Centralis, 2020)
NORMATIVE LEXICOGRAPHY AT THE FRAN RAMOVŠ INSTITUTE OF THE SLOVENIAN LANGUAGE AT ZRC SAZU In this article we present the normative activity of the Lexicological Section of The Fran Ramovš Institute of the Slovenian Language at ZRC SAZU. In particular, the researchers investigate the codifcation of linguistic standards developed in the second half of the 20th century and early 21st century. Whereas Slovenian normative guides of the 20th century had twofold function, serving as an orthographic guide as wellas a monolingual explanatory dictionary, the normative guide of the 21st century needs to be created in a digital environment and therefore organised as language database providing normative information. Finally, some of the issues of database design are discussed.